Optimization Strategy for Zakat Collection and Distribution in the Digital Era - Efendi Sugianto (Journal of Islamic Economy, 2025)
This study aims to analyze the strategy for optimizing zakat collection and distribution in the digital era, especially in the context of efficiency, transparency, and service reach. The background of this study is the still low realization of zakat collection compared to the very large national potential, as well as the challenges of unequal zakat distribution. The research method used is qualitative descriptive with data collection techniques in the form of in-depth interviews, document studies, and secondary data analysis from zakat institutions and other relevant sources. The results of the study show that digitalization of zakat through applications, e-wallets, and online payment systems can increase ease of access for muzakki and expand the reach of distribution to mustahik. Transparency of digital reports also encourages public trust, while infrastructure challenges and digital literacy remain obstacles that need to be overcome. This study emphasizes the importance of collaboration between the government, zakat institutions, and the technology sector to build an effective zakat system in the digital era.The findings of this study indicate that the use of digital technology, such as mobile-based zakat applications, QRIS systems, e-wallets, and online payments, have made a real contribution to increasing ease of access for muzakki and streamlining the zakat fund collection process. Furthermore, zakat distribution has become more structured and more widely accessible due to the integration of data and technology-based tracking systems. In addition, the transparency of real-time digital reports has been proven to increase the level of public trust in zakat institutions. However, this study also found that infrastructure challenges, technological gaps between regions, and low digital literacy, both among zakat managers and recipients, are still serious obstacles in efforts to optimize the digital zakat system.